2018
DOI: 10.1111/irv.12521
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilization and cost of influenza requiring hospitalization in Canadian adults: A study from the serious outcomes surveillance network of the Canadian Immunization Research Network

Abstract: BackgroundConsideration of cost determinants is crucial to inform delivery of public vaccination programs.Objectives to estimate the average total cost of laboratory‐confirmed influenza requiring hospitalization in Canadians prior to, during, and 30 days following discharge. To analyze effects of patient/disease characteristics, treatment, and regional differences in costs.MethodsStudy utilized previously recorded clinical characteristics, resource use, and outcomes of laboratory‐confirmed influenza patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 11 publications
2
37
2
Order By: Relevance
“…Similar to the US study of Young-Xu et al estimating costs of influenza-attributed hospitalizations [46], we found the highest costs in the age group 45-64 years. Although higher hospitalization costs are largely driven by LOS [44], mean LOS in our study was actually higher in the ≥ 75 age group. Nevertheless, the highest hospitalization costs per patient in the age group 45-64 years can be partly explained by the highest percentage of ICU admissions and the longest stay per admitted ICU patient.…”
Section: Costscontrasting
confidence: 57%
See 1 more Smart Citation
“…Similar to the US study of Young-Xu et al estimating costs of influenza-attributed hospitalizations [46], we found the highest costs in the age group 45-64 years. Although higher hospitalization costs are largely driven by LOS [44], mean LOS in our study was actually higher in the ≥ 75 age group. Nevertheless, the highest hospitalization costs per patient in the age group 45-64 years can be partly explained by the highest percentage of ICU admissions and the longest stay per admitted ICU patient.…”
Section: Costscontrasting
confidence: 57%
“…Comparison with other studies is difficult due to differences in healthcare system, applied resource unit cost, case definition, study population, and/or taking readmissions into account. Differences in healthcare system and resource unit prices [37][38][39][40] are illustrated by a Spanish [41], Italian [42], German [43] and Canadian study [44]. In Spain, despite a longer arithmetic mean LOS (11.1 days), a lower arithmetic mean costs per influenza hospitalization (in 2015 euros) in patients aged ≥ 65 years (€3219) was reported.…”
Section: Costsmentioning
confidence: 99%
“…Furthermore, 15% of older adults admitted with laboratory-confirmed influenza will experience catastrophic disability with a loss of independence in more than two basic self-care activities [30] and older adults are also vulnerable to diminished quality of life due to loss of independence following hospitalization with influenza [25]. In fact, influenza accounts for nearly 30% of all disability-adjusted life years lost to infectious disease [31], and influenza hospitalization is estimated to cost more than 2 billion dollars in Canada over the next decade [32]. Older adults, especially those living with chronic conditions and/or frailty, are highly susceptible to severe outcomes of influenza; however, the correlates of protection in this vulnerable population are not well investigated.…”
Section: Burden Of Influenzamentioning
confidence: 99%
“…During this period, influenza A represented 87.3% of all laboratory-confirmed influenza cases [17]. We estimated hospitalization rates from an health administrative data study on influenza for influenza-confirmed patients in Canada [18]. We used hospitalization rates resulting from influenza only, and assumed that patients with ILI and not severely ill were not hospitalized (i.e., discharged home).…”
Section: Parameters and Key Assumptionsmentioning
confidence: 99%
“…We assumed the hospital setting invested in start-up and capital costs for all diagnostic tests and rapid diagnostic tests did not require lab technician time. All healthcare utilization costs related to influenza were extracted from an administrative data study from the Canadian Immunisation Research Network [18]. A complete course of oseltamivir treatment was $42, which was calculated using Ontario Drug Benefit list prices and current recommended treatment algorithms [9,24].…”
Section: Parameters and Key Assumptionsmentioning
confidence: 99%